Curbing Teenage Pregnancy in South Africa’s Schools - Umubyeyi, Beatrice Samson (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Teenage pregnancy in South African schools presents a significant challenge to the education system and society as a whole. This study seeks to investigate the strategies implemented to decrease teenage pregnancy in South African schools. It is based on qualitative secondary sources such as expert analysis, teacher input, civil society, and testimonies from teenagers. The data was collected from public online sources, including audio, YouTube videos, and written testimonies. The findings indicate that teenage pregnancy has reached a crisis point. Socioeconomic challenges such as poverty, unemployment, peer pressure, cultural and societal norms around sexuality, and related challenges are at the center of child pregnancy in South Africa.